Method for deacidifying paper by using hydroxyapatite

By atomizing spraying and dry heat aging treatment of hydroxyapatite aqueous suspension on paper, the problems of insufficient alkali reserves and high cost in the existing paper deacidification methods are solved, and decay is comparable to that of commonly used deacidifiers. Acid effect and improves the physical properties of the paper and delays the aging process.

CN119121691AActive Publication Date: 2024-12-13SOUTH CHINA UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411079431.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2024-12-13
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

In the existing paper deacidation methods, alkaline gas has small alkali reserves and is dangerous to burn. Although liquid phase deacidants such as calcium hydroxide and calcium carbonate are commonly used, they have large alkali reserves and high cost, and lack effective hydroxyapa. The stone spray method is difficult to effectively neutralize the acidic substances in the paper, resulting in accelerated paper aging.

Method used

Hydroxyapatite (HA) water suspension is uniformly sprayed on the paper surface by atomization spraying method, and then naturally dry and balance the moisture in a constant temperature and humidity chamber, dry heat aging treatment is used to synthesize HA through chemical precipitation method. Improve the deacidification effect.

Benefits of technology

A similar deacidification effect as commonly used deacidants such as calcium carbonate and calcium hydroxide is achieved. The physical performance improvement after dry heat aging is achieved, the paper aging process is delayed, the paper fold resistance and breathability are improved, and the chemical is shown. The deacidification effect of precipitation HA is better than that of commercial HA.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121691A_ABST
    Figure CN119121691A_ABST
Patent Text Reader

Abstract

The invention discloses a method for deacidifying paper by using hydroxyapatite. The method comprises the following steps: selecting 0.05%-0.5% by mass of HA water suspension, uniformly spraying the liquid to the surface of filter paper by adopting an atomizing and spraying method, and after spraying, horizontally placing the filter paper in air for 1-12 hours, preferably 5 hours; naturally volatilizing the moisture, then placing in a constant-temperature and constant-humidity chamber to balance the moisture for 12-48 hours, preferably 24 hours, and detecting; the source of the HA is a reagent synthesized by a chemical precipitation method or a commercialized reagent. According to the invention, the HA dispersion liquid is sprayed on the surface of the paper by adopting an atomization spraying method, so that a deacidification effect which can be comparable with calcium carbonate and calcium hydroxide is obtained. After the paper is further treated by a dry heat aging method, the physical properties of the paper deacidified by the chemical precipitation method HA are even reversely improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of paper deacidification, and in particular relates to a method for deacidifying paper by using hydroxyapatite. Background Art

[0002] Paper documents such as ancient books and archives are an important part of Chinese traditional culture, the main carrier of traditional culture and historical information, and the witness of Chinese culture and history. They have extremely high historical value, cultural value and academic value. Therefore, the protection of paper documents is very important.

[0003] Over time, paper will age irreversibly, mainly manifested by increased acidity (decreased pH), decreased mechanical strength, color change, breakage, and even brittleness. In essence, paper aging is caused by the breakage of β-1,4-glycosidic bonds between cellulose sugar rings, which causes a decrease in the degree of polymerization (DP) of cellulose. The fundamental reason is acid catalysis; insect and fungal erosion cannot be ignored. There are many sources of acid: on the one hand, due to changes in temperature and humidity, heat and ultraviolet radiation, cellulose and hemicellulose in paper will slowly degrade and produce endogenous acidic substances; on the other hand, and more importantly, the fillers added to paper, the sizing agents coated on the surface, the ink used for writing, and air pollutants will produce a large amount of acidic substances, which greatly accelerates the aging of paper. Especially since modern times, my country has introduced Western papermaking technology, paper is made by machine, and aluminum sulfate-rosin is used as a sizing agent, which has caused the fastest aging rate in modern documents (late 19th century to mid-20th century), so its protection is imminent.

[0004] The best way to protect acidified documents is to perform deacidification. Deacidification refers to the introduction of alkaline substances into paper documents, which can neutralize existing acidic substances and form alkaline reserves, which can continue to neutralize acidic substances produced in the future. Deacidification is the main method to delay paper degradation and extend the life of paper. The current deacidification methods include gas phase method and liquid phase method. Gas phase deacidification mainly uses alkaline gas, but the alkali reserves are small and sometimes there is a risk of combustion. Liquid phase deacidification is more commonly used, including aqueous solutions and organic solutions. The alkaline substances contained in the solution can play a neutralizing role. The most commonly used substances include: calcium hydroxide, calcium carbonate, magnesium hydroxide, magnesium oxide, etc. However, the method of adding hydroxyapatite (HA) to acidified paper using liquid phase spray has not been reported. HA is the most stable calcium-phosphorus mineral and also carries hydroxide (OH - ), which can neutralize acidic substances and remain stable for a long time. HA also contains phosphate (PO4 3- ) and OH -, which is conducive to the formation of more hydrogen bonds and achieve better bonding with paper. Summary of the invention

[0005] The present invention overcomes the above-mentioned defects and provides a method for deacidifying paper using hydroxyapatite. The present invention uses an atomized spraying method to spray HA dispersion on the surface of paper, thereby obtaining a deacidification effect comparable to that of calcium carbonate and calcium hydroxide. After further treatment by a dry heat aging method, the physical properties of the paper deacidified by HA using a chemical precipitation method are even improved in the opposite direction.

[0006] The technical solution of the present invention is as follows.

[0007] A method for deacidifying paper using hydroxyapatite, wherein the mass percentage concentration of HA water suspension is 0.05% to 0.5%, preferably 0.1%, and the liquid is evenly sprayed onto the surface of filter paper by atomization spraying method. After spraying, the paper is placed horizontally in the air for 1 hour to 12 hours, preferably 5 hours; the water is naturally evaporated, and then the paper is placed in a constant temperature and humidity chamber for 12 hours to 48 hours, preferably 24 hours, to balance the water content, and then tested;

[0008] The temperature of the constant temperature and humidity chamber is 23°C to 27°C, preferably 26°C, and the humidity is 40-60%;

[0009] The source of the HA is a chemical precipitation synthesis or commercial reagent.

[0010] A method for deacidifying paper using hydroxyapatite, the method for synthesizing HA by chemical precipitation is as follows:

[0011] 1) preparing a calcium source and a phosphorus source;

[0012] 2) adding polyethylene glycol 6000 (PEG6000) to the calcium source and stirring continuously; then adding ammonia water to make the pH value of the calcium source greater than 11;

[0013] 3) Turn on the heating to keep the calcium source at 60°C; turn on the peristaltic pump and slowly add the phosphorus source to the calcium source. The addition takes 2 to 5 hours and the stirring is continued;

[0014] 4) Aging at room temperature to complete the reaction;

[0015] 5) Centrifuge and discard the supernatant;

[0016] 6) Add deionized water to the precipitate for washing, centrifuge, discard the supernatant, and repeat the washing process; wash with anhydrous ethanol;

[0017] 7) Dry in an oven and grind to obtain the finished product.

[0018] In the above method, in step 1), the calcium source is a 0.5 mol / L Ca(NO3)2·4H2O solution.

[0019] In the above method, in step 1), the phosphorus source is 0.25 mol / L (NH4)3PO4·3H2O.

[0020] In the above method, in step 2), the mass percentage concentration of polyethylene glycol 6000 in the calcium source is 0.01% to 0.3%, preferably 0.1%; and the stirring time is 15 min to 60 min.

[0021] In the above method, in step 4), the aging time is 12h to 72h.

[0022] In the above method, in step 6), the repeated washing is 1 to 3 times; the washing with anhydrous ethanol is 1 to 3 times.

[0023] In the above method, in step 7), the drying temperature is 50° C. to 80° C., preferably 60° C.; the drying time is 3 h to 18 h, preferably 12 h.

[0024] Compared with the prior art, the advantages of the present invention are:

[0025] 1. Ca(OH)2 and CaCO3 are currently commonly used paper deacidification agents. Overall, the difference in physical properties between commercial HA, chemical precipitation HA and commercial Ca(OH)2 and commercial CaCO3 deacidification filter paper is small, indicating that the deacidification effect of HA is equivalent to that of Ca(OH)2 and CaCO3. However, the alkali reserve of HA is much lower than that of Ca(OH)2 and CaCO3 (only about 1 / 10), so this result is unexpected.

[0026] 2. Overall, after 5 days of dry heat aging, the deacidification effect of HA is still comparable to that of CaCO3, and even better than that of Ca(OH)2 (the filter papers deacidified by Ca(OH)2 and CaCO3 were not further dry heat aged). Therefore, the short-term dry heat method, which was originally used to accelerate aging, can be used as a means to improve the deacidification effect of HA, producing unexpected results.

[0027] 3. After further treatment with dry heat aging, the physical properties of the paper deacidified by chemical precipitation HA even improved in the opposite direction, producing an unexpected effect without any technical inspiration.

[0028] 4. The deacidification effect of HA by chemical precipitation method is better than that of commercial HA, which produces unexpected results. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1a Infrared spectra of commercial sources;

[0030] Figure 1bThis is the infrared spectrum of the chemical precipitation method;

[0031] Figure 2 Physical properties of acidified filter paper and blank filter paper repaired with commercial HA, chemical precipitation HA, commercial Ca(OH)2, and commercial CaCO3: a, whiteness, b, tensile index, c, tear index, d, folding resistance, e, air permeability (air permeability between 25 and 30 is more suitable);

[0032] Figure 3 The physical properties of the acidified filter paper repaired with commercial HA and chemical precipitation HA and the blank acidified filter paper after 5 days of dry heat aging are compared: a, whiteness, b, tensile index, c, tear index, d, folding endurance, e, air permeability (the air permeability is more suitable between 25 and 30). The green columns without hatching are the results before dry heat aging, and the purple columns with hatching are the results after dry heat aging.

[0033] Figure 4 The morphology of HA under scanning electron microscope, where a is commercial source and b is chemical precipitation method. DETAILED DESCRIPTION

[0034] Example 1

[0035] (1) Acidification method: Use Whatman qualitative filter paper (diameter 18 cm) and spray with 0.03% aluminum sulfate aqueous solution. Use pressure atomization to spray the liquid evenly onto the surface of the filter paper. Place it horizontally in the air for 5 hours to naturally evaporate the water. Then place it in a constant temperature and humidity chamber (temperature 26°C, humidity 40-60%) to balance the water for 24 hours before testing.

[0036] (2) Deacidification method: The concentration of the selected HA aqueous suspension is 0.1%, and the concentration of the calcium carbonate aqueous suspension and the calcium hydroxide aqueous solution is also 0.1%. There are two sources of HA, namely chemical precipitation synthesis and commercial reagents (manufacturer: Shanghai McLean Biochemical Technology Co., Ltd.; item number: H875582; batch number: C14767668). The above solutions / suspensions were tested separately, and the spraying method was still selected. During spraying, the atomized spray method is used to evenly spray the liquid onto the surface of the filter paper. After spraying, place it horizontally in the air for 5 hours to naturally evaporate the moisture. Then place it in a constant temperature and humidity chamber (temperature 26°C, humidity 40-60%) to balance the moisture for 24 hours and then test it.

[0037] In this embodiment, the method for synthesizing HA by chemical precipitation is as follows: HA is synthesized according to the following steps. 1) Prepare 1L of 0.5mol / L Ca(NO3)2·4H2O solution and 0.25mol / L (NH4)3PO4·3H2O solution, respectively, as calcium source and phosphorus source. 2) Add polyethylene glycol 6000 (PEG6000) to the calcium source at a concentration of 0.1%, and stir continuously for 30min; then add ammonia water to make the pH value of the calcium source greater than 11. 3) Turn on the heating to keep the calcium source at 60°C; turn on the peristaltic pump, slowly add the phosphorus source to the calcium source, add it in 3 hours, and continue stirring. 4) Aging at room temperature for 24h to complete the reaction. 5) Centrifuge and pour off the supernatant. 6) Add deionized water to the precipitate for washing, centrifuge, discard the supernatant, repeat the washing once; wash once with anhydrous ethanol. 7) Dry in an oven at 60°C for 12h, grind, and obtain the finished product.

[0038] Alkali reserve detection method: Detection is carried out in accordance with GB / T 24998-2010. Cut the filter paper into small pieces, add deionized water and heat to a slight boil. Add an excess of 0.1 mol / L HCl solution to neutralize the alkaline substance, add 1 drop of methyl red indicator, and then use 0.1 mol / L NaOH solution to back-titrate the remaining hydrochloric acid. The change from pink to light yellow is regarded as the titration end point, and the alkali reserve is calculated.

[0039] The composition of HA was confirmed by infrared spectroscopy (IR), and the morphology of HA was observed by scanning electron microscopy (SEM).

[0040] Example 2

[0041] The composition of HA was confirmed by infrared spectroscopy (IR), and the morphology of HA was observed by scanning electron microscopy (SEM).

[0042] Confirmation of HA ingredients

[0043] In Example 1, the infrared spectra of chemical precipitation method and commercial HA (Figure 1) are 1033, 1096, 565, 3570 cm -1 The characteristic peaks of HA can be clearly identified, so both are pure hydroxyapatite. The scanning electron microscope (SEM) photos of commercial HA and chemical precipitation HA are shown in Figure 4 As can be seen from the figure, commercial HA basically presents the morphology of micron-sized particles, and a few particles are nano-sized. However, chemical precipitation HA basically presents a nano-sized needle-like morphology with a smaller particle size. Therefore, the smaller particle size of chemical precipitation HA may make it better dispersed inside the paper fiber, thereby achieving a better deacidification effect.

[0044] Example 3

[0045] This example compares the deacidification effects of commercial HA, chemical precipitation HA, commercial Ca(OH)2, and commercial CaCO3:

[0046] The repair effect of four substances on acidified filter paper was investigated. Figure 2 . For whiteness, commercial HA, chemical precipitation HA and commercial CaCO3 are equivalent, which is better than the effect of commercial Ca(OH)2. For tensile index, commercial HA, chemical precipitation HA and commercial CaCO3 are equivalent, which is worse than the effect of commercial Ca(OH)2. For tear index, commercial HA, chemical precipitation HA and commercial Ca(OH)2 and commercial CaCO3 are equivalent, but the average values ​​of commercial HA and chemical precipitation HA are higher. For folding endurance, commercial HA and chemical precipitation HA are worse than the effect of commercial Ca(OH)2 and commercial CaCO3. For air permeability, there are significant differences between commercial HA, chemical precipitation HA and commercial Ca(OH)2 and commercial CaCO3; however, the suitable range of air permeability is between 25 and 30, and commercial HA and chemical precipitation HA are exactly in this range, while commercial Ca(OH)2 and commercial CaCO3 are greater than 30.

[0047] Overall, the differences in physical properties between commercial HA, chemical precipitation HA, commercial Ca(OH)2, and commercial CaCO3 deacidified filter paper are small, indicating that the deacidification effect of HA is comparable to that of Ca(OH)2 and CaCO3. However, the alkali reserve of HA is much lower than that of calcium hydroxide and calcium carbonate (only about 1 / 10), so this result is unexpected. For air permeability, the value of HA deacidified filter paper is between 25 and 30, which is more in line with the requirements of paper repair than calcium hydroxide and calcium carbonate.

[0048] Example 4

[0049] The result of continued dry heat aging

[0050] The filter paper that has been sprayed with HA deacidification agent and the blank filter paper that has been acidified are tested by dry heat aging for 5 days. Figure 3. Because dry heat produces an accelerated aging effect, the physical properties of paper usually decrease. For example, when calcium carbonate is used for deacidification, whiteness, tensile strength, tear strength, and folding resistance all decrease after dry heat aging (Qi Shi. Study on the in-situ formation of calcium carbonate and its effect on deacidification of aged paper [D]. Guangzhou: South China University of Technology, 2022.). For the two indicators of whiteness and tear strength, the commercial HA and chemical precipitation HA deacidified filter papers both decreased, which was consistent with expectations. However, for tensile strength, after dry heat treatment, the commercial HA and chemical precipitation HA deacidified filter papers did not decrease but increased, and the chemical precipitation HA deacidified filter papers had significant differences. For folding resistance, the commercial HA deacidified filter paper showed a slight decrease; but the chemical precipitation HA deacidified filter paper showed a significant increase, and there was a significant difference, which was unexpected. For air permeability, the commercial HA and chemical precipitation HA deacidified filter papers did not change significantly after dry heat treatment, and both were in the appropriate range of 25 to 30.

[0051] Overall, after 5 days of dry heat aging, the deacidification effect of HA is still comparable to that of calcium carbonate, and even better than that of calcium hydroxide (the filter papers deacidified by calcium carbonate and calcium hydroxide have not been dry heat aged). Therefore, the short-term dry heat method, which was originally used to accelerate aging, can be used as a means to improve the deacidification effect of HA, especially chemical precipitation HA. On the other hand, under natural conditions, HA has a better ability to resist long-term aging.

[0052] Example 4

[0053] This example compares the deacidification effects of commercial HA and chemical precipitation HA:

[0054] The present invention also compares the deacidification effect of commercial HA and chemical precipitation HA. Before dry heat treatment, the deacidification effect of chemical precipitation HA is better than that of commercial HA. The whiteness, tensile index and tear index of filter paper treated with chemical precipitation HA are higher than those of commercial HA, and the folding resistance and air permeability are equivalent. After dry heat treatment, both whiteness and tear index decreased synchronously; both tensile index increased synchronously; in terms of folding resistance index, filter paper treated with chemical precipitation HA showed a significant improvement, while filter paper treated with commercial HA did not change; for air permeability index, both did not change. Therefore, the deacidification effect of chemical precipitation HA is better than that of commercial HA.

Claims

1. A method for deacidifying paper using hydroxyapatite, characterized in that: The mass percentage concentration of HA water suspension is selected to be 0.05% to 0.5%. The liquid is evenly sprayed onto the surface of the filter paper by atomization spraying method. After spraying, it is placed horizontally in the air for 1h to 12h to naturally evaporate the water, and then placed in a constant temperature and humidity chamber for 12h to 48h to balance the water content before testing; The temperature of the constant temperature and humidity chamber is 23°C to 27°C, and the humidity is 40-60%; The source of the HA is a chemical precipitation synthesis or commercial reagent.

2. A method for deacidifying paper using hydroxyapatite according to claim 1, characterized in that: The mass percentage concentration of the HA water suspension is 0.1%; and the horizontal placement time is 5 hours.

3. The method for deacidifying paper using hydroxyapatite according to claim 1, characterized in that: The moisture balance time is 24 hours; the temperature of the constant temperature and humidity chamber is 26°C.

4. The method for deacidifying paper using hydroxyapatite according to claim 1, characterized in that: The method for synthesizing HA by chemical precipitation is as follows: 1) preparing a calcium source and a phosphorus source; 2) adding polyethylene glycol 6000 (PEG6000) to the calcium source and stirring continuously; then adding ammonia water to make the pH value of the calcium source greater than 11; 3) Turn on the heating to keep the calcium source at 60°C; turn on the peristaltic pump and slowly add the phosphorus source to the calcium source. The addition takes 2 to 5 hours and the stirring is continued; 4) Aging at room temperature to complete the reaction; 5) Centrifuge and discard the supernatant; 6) Add deionized water to the precipitate for washing, centrifuge, discard the supernatant, and repeat the washing process; wash with anhydrous ethanol; 7) Dry in an oven and grind to obtain the finished product.

5. The method for deacidifying paper using hydroxyapatite according to claim 2, characterized in that: In step 1), the calcium source is a 0.5 mol / L Ca(NO3)2·4H2O solution.

6. The method for deacidifying paper using hydroxyapatite according to claim 2, characterized in that: In step 1), the phosphorus source is 0.25 mol / L (NH4)3PO4·3H2O.

7. The method for deacidifying paper using hydroxyapatite according to claim 2, characterized in that: In step 2), the mass percentage concentration of polyethylene glycol 6000 in the calcium source is 0.01% to 0.3%; and the stirring time is 15 min to 60 min.

8. The method for deacidifying paper using hydroxyapatite according to claim 2, characterized in that: In step 4), the aging time is 12h to 72h.

9. The method for deacidifying paper using hydroxyapatite according to claim 2, characterized in that: In step 6), the washing is repeated 1 to 3 times; and the washing with anhydrous ethanol is washed 1 to 3 times.

10. The method for deacidifying paper using hydroxyapatite according to claim 2, characterized in that: In step 7), the drying temperature is 50° C. to 80° C. and the drying time is 3 h to 18 h.

Citation Information

Patent Citations

  • Hydroxyapatite and preparation method thereof

    CN102849700A

  • Preparation method of silicon-doped alpha-tricalcium phosphate ceramic

    CN104557015A

  • Groove type ultrasonic equipment and applications thereof

    CN107604757A

  • Preparation method of multifunctional paper repair liquid of bacterial cellulose-based alkaline nanoparticles and application of multifunctional paper repair liquid in repair of aged paper

    CN113802411A

  • Preparation method and application of nano calcium carbonate stable dispersion liquid

    CN117661368A